On a More Accurate Half-Discrete Mulholland-Type Inequality Involving One Multiple Upper Limit Function - Xianyong Huang; Bicheng Yang (Journal of Function Spaces)
By the use of the weight functions, the symmetry property, and Hermite-Hadamard’s inequality, a more accurate half-discrete Mulholland-type inequality involving one multiple upper limit function is given. The equivalent conditions of the best possible constant factor related to multiparameters are studied. Furthermore, the equivalent forms, several inequalities for the particular parameters, and the operator expressions are provided.